Global Perspectives on Precision Medicine Ethical, Social and Public Health Implications - Sarwar, Evangel (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents the promises of Precision Medicine (PM) and the challenges of its implementation in daily clinical routine, while addressing the anticipated ethical and social implications. It is the first book that critically analyzes the potential and the dilemmas relevant to genomics and precision medicine from healthcare, public health and global perspectives. The nine chapters presented in this book elaborate on pharmacogenomics' crucial role in maximizing the potential benefits and minimizing medication's potential risks in groups of people, especially in cancer treatment and other health conditions. Infectious and non-communicable diseases (NCDs) are also discussed in this book by identifying challenges and ways to overcome them. Essential concepts are addressed, such as health-related benefits and harm to individuals and the broader community, including threats to individual privacy and autonomy, which warrant just distribution of scarce resources. The book also identifies and addresses the lack of competency in the healthcare workforce in the era of PM and discusses the path to laying the ethical foundation for the implementation of PM in healthcare organizations.
Chapter 1: Introduction -- Chapter 2: The Emerging Field of Precision Medicine - The New Paradigm for Healthcare -- Chapter 3: Clinical Significance of Precision Medicine - Genomics and Pharmacogenomics (PGx) -- Chapter 4: Relevance of PM in Infectious and Non-communicable Chronic Diseases and Pandemics -- Chapter 5: Relevance of PM in Public Health Genomics and Global Health Genomics -- Chapter 6: Social and Ethical Implications of Integrating Precision Medicine into Healthcare -- Chapter 7: Laying an Ethical Foundation in Healthcare in the era of PM -- Chapter 8: Education and Competency Rich in Genomics and Ethics is a Necessity for Healthcare Professionals in the Era of PM -- Chapter 9: Concluding Thoughts -- Bibliography -- End Notes.
Keywords: Bioethics; Public health; Medicine, Preventive; Health promotion; Medical sciences; Bioethics; Public Health; Health Promotion and Disease Prevention; Health Sciences